Effects of Led Supplementary Lighting and NPK Fertilization on Fruit Quality of Melon (Cucumis melo L.) Grown in Plastic House - Somsak Kramchote; Somchai Glahan (My University, 2020)
Abstract Melon ( Cucumis melo L.) is a high-value fruit in Thailand, usually grown in plastic houses where light could become a major limiting growth factor. This study used melon cultivar ‘#120’ (orange flesh) grown in a plastic house under natural daylight (NDL, control) and with supplementary lighting using light emitting diodes (LEDs) of a combination of red 630 nm, red 660 nm, blue 450 nm, blue 460 nm, white 14000 K, UV 410 nm and IR 730 nm (LED1) or a combination of red 630 nm, red 660 nm, blue 450 nm and blue 460 nm (LED2) applied for 12 h from 6:00 pm to 6:00 am. These lighting treatments were combined with NPK fertilization using complete fertilizer 15–15–15 (N–P 2 O 5 –K 2 O) at 5 g, 7 g (recommended rate) or 9 g per plant. Results showed that LED2 combined with 9 g 15–15–15 was the most effective in increasing plant height, chlorophyll content (SPAD index), fruit size and mass, and peel and flesh thickness. The fruit also developed the desired lighter color (higher L* and lower a* coordinates) and were the firmest and sweetest (highest soluble solids content and lowest titratable acidity) among all treatments.
Keywords: Melon; Cucumis; Cyan; Titratable acid; Red cabbage; Flesh; Light effects on plants